ABA therapies in Autism: Unique solution for a multiple problem? - Valencia-Cifuentes, Valeria (2019)
The “Clinical Protocol for the diagnosis, treatment and comprehensive care route of children with Autism Spectrum Disorders (ASD)” was published in Colombia in 2015, in order to improve the quality of care and the prognosis of people with ASD in the country. This Protocol has as a therapeutic focus the Applied Behavior Analysis (ABA), which is based on the modification of behaviors considered as disruptive or aberrant in people within the spectrum. The ASD has increased its global prevalence drastically and this article proposes a reflection on the need to consider additional interventions to the ABA that can guarantee a coverage of the therapeutic needs of the patients, given that it is an entity with multifactorial etiology, where they enter at stake genetic and epigenetic factors, as well as a high symptomatic heterogeneity in the groups of patients.